ANALISIS KESALAHAN DALAM MENYELESAIKAN SOAL SUDUT, LUAS, DAN KELILING SEGITIGA SISWA KELAS VII SMP NEGERI 2 MLATI, SLEMAN - Amalia sulistyowati; A. A Sujadi (UNION: Jurnal Ilmiah Pendidikan Matematika, 2015)
The purposes of this study were to determine: (1) The percentage of error in understanding questions, (2) The percentage of eror in the application of mathematical concepts and principles, (3) The percentages of error in computation, and (4) The most common type of error made by students in answering questions about angle, area, and circumference of triangle. The study population was seventh grade students of SMP Negeri 2 Mlati in Sleman Regency. The technique of sample was Cluster Sampling. The result of analysis showed that: (1) The percentage of error in understanding questions is 12,95% with very low category, (2) The percentage of eror in the application of mathematical concepts and principles is 59,82% with sufficient category, (3) The percentages of error in computation is 30,80% with low category and (4) The most common type of error made by students is application of mathematical concepts and principles. From the analysis it can be concluded that students still make some mistakes in answering questions about angle, area, and circumference of triangle, especially on the type of application error of mathematical concepts and principles.